2016
DOI: 10.15171/bi.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Association study of IL2RA and CTLA4 Gene Variants with Type I Diabetes Mellitus in children in the northwest of Iran Association study of IL2RA and CTLA4 gene variants with type-1 diabetes mellitus in children in the northwest of Iran

Abstract: Introduction: A variety of genetic predisposing factors and environmental factors are known to influence the pathogenesis of type-1 diabetes (T1D). This study intended to investigate the association of cytotoxic T-lymphocyte associated protein 4 (CTLA4) and interleukin 2 receptor subunit alpha (IL2RA) gene polymorphisms with type 1 diabetes in children of northwest of Iran. Methods: Genomic DNA was extracted by salting-out method. PCR amplification and direct sequencing methods were used for genotyping of CTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Our study found that the frequency of G allele and GG homozygous genotype was significantly high in patients than in controls ( p = 0.01). This finding consistent with previous studies in populations from our continent includes Egyptians 16 18 and Tunisians, 19 together with other populations such as Indian, 20 Caucasian and Asian, 21 22 Iranians, 23 24 25 Estonian and Finnish, 26 Chilean, 27 and Russian. 28 Other studies among Sudanese, 9 Ghanaian, 29 and other populations, 30 31 did not prove this association.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found that the frequency of G allele and GG homozygous genotype was significantly high in patients than in controls ( p = 0.01). This finding consistent with previous studies in populations from our continent includes Egyptians 16 18 and Tunisians, 19 together with other populations such as Indian, 20 Caucasian and Asian, 21 22 Iranians, 23 24 25 Estonian and Finnish, 26 Chilean, 27 and Russian. 28 Other studies among Sudanese, 9 Ghanaian, 29 and other populations, 30 31 did not prove this association.…”
Section: Discussionsupporting
confidence: 93%
“…We studied the CTLA-4 (+49 A/G) polymorphism because it has been the most widely analyzed variant in different ethnic groups, and still with inconsistent findings. 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 Furthermore, this is the first study investigated the effect of +49A/G polymorphism among Sudanese children with T1DM, bearing in mind a recent data investigated this polymorphism among Sudanese adults with T1DM. 9 …”
Section: Discussionmentioning
confidence: 92%
“…Alterações genéticas, principalmente na região do complexo maior de histocompatibilidade (MHC). Além do MHC, outros genes possuem relação com o desenvolvimento deste distúrbio, como polimorfismos nos genes que codificam a insulina (INS), CTLA4, PTPN2 e IL2RA que possuem maior chance de mutação em populações específicas como asiáticos e causasianos (Ikegami et al, 2008;Ranjouri et al, 2016;Van Belle et al, 2011).…”
Section: Genes Envolvidos Na Predisposição Genética Associada Ao Dm1unclassified
“…46,47 Multiple studies have noted predisposing role for minor G allele of this polymorphism for CD 18 and T1D. [13][14][15][19][20][21][22][23][24] Two studies; Mora et al, Naluai et al 16,17 have observed the higher risk of CD in individuals bearing the wild-type A allele of this polymorphism. On the other hand, some have not reported any significant association between this polymorphism with the occurrence of CD 12,13 and T1D.…”
Section: Cytotoxic T-lymphocyte Associated Proteinmentioning
confidence: 99%